Synthesis of the External Non-Circular Gear-Train with Cycloid Profile - Nguyen, Hong Thai; Nguyen, Thanh Trung; Luu, Xuan Nghia; Nguyen, Thuy Duong (Old Journal, 2020)
Non-circular gears have recently been researched and developed for converting movement in some special cases as well as in continuously variable transmission. However, most of the research on this topic are focused on the non-circular gears with involute profile. In order to design the non-circular gear-train with cycloidal profile (including epicycloid and hypocycloid), the authors present a method to determine profile of the non-circular gear based on application of the cylindrical cycloidal eccentric gearing combining with meshing condition of the gearing theory. The achieved results of this work are useful for manufacture of the new non-circular gear-trains.